Calcium-sensing receptor regulates stomatal closure through hydrogen peroxide and nitric oxide in response to extracellular calcium in Arabidopsis - Wang, Wen-Hua (Oxford University Press, 2012)
The Arabidopsis calcium-sensing receptor CAS is a crucial regulator of extracellular calcium-induced stomatal closure. Free cytosolic Ca(2+) (Ca(2+)(i)) increases in response to a high extracellular calcium (Ca(2+)(o)) level through a CAS signalling pathway and finally leads to stomatal closure. Multidisciplinary approaches including histochemical, pharmacological, fluorescent, electrochemical, and molecular biological methods were used to discuss the relationship of hydrogen peroxide (H(2)O(2)) and nitric oxide (NO) signalling in the CAS signalling pathway in guard cells in response to Ca(2+)(o). Here it is shown that Ca(2+)(o) could induce H(2)O(2) and NO production from guard cells but only H(2)O(2) from chloroplasts, leading to stomatal closure. In addition, the CASas mutant, the atrbohD/F double mutant, and the Atnoa1 mutant were all insensitive to Ca(2+)(o)-stimulated stomatal closure, as well as H(2)O(2) and NO elevation in the case of CASas. Furthermore, it was found that the antioxidant system might function as a mediator in Ca(2+)(o) and H(2)O(2) signalling in guard cells. The results suggest a hypothetical model whereby Ca(2+)(o) induces H(2)O(2) and NO accumulation in guard cells through the CAS signalling pathway, which further triggers Ca(2+)(i) transients and finally stomatal closure. The possible cross-talk of Ca(2+)(o) and abscisic acid signalling as well as the antioxidant system are discussed.